Comprehensive analysis of lysine lactylation and its potential biological significance in clear cell renal cell carcinoma - Bangbei Wan; Yuan Huang; Binghao Gong; Yaohui Zeng; Cai Lv (European Journal of Medical Research)
Abstract Background Clear cell renal cell carcinoma (ccRCC) is a common histological subtype of malignant renal neoplasm. Protein lysine lactylation (Kla) plays a crucial role in tumor metabolic reprogramming. However, little is known regarding the distribution and potential biological functions of Kla in ccRCC. This study aimed to systematically investigate the role of Kla in ccRCC. Methods A total of 12 ccRCC samples were collected from 6 patients. Western blotting was performed to determine the trend of Kla-modified proteins in ccRCC. Liquid chromatography–tandem mass spectrometry was used to quantitatively analyze Kla in ccRCC. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein–protein interaction (PPI) network analyses were conducted to clarify the biological functions and interactional relationships of differentially lactylated proteins (DLPs). Results In total, 239 DLPs, including 441 lactylated sites, were identified by comparing ccRCC tissues with adjacent normal tissues. Kla-related enzymes have a higher affinity for alanine than for other amino acid residues in ccRCC. Subcellular localization analysis revealed that most DLPs were localized in the cytoplasm and mitochondria. GO enrichment analysis showed that most of the DLPs were enriched in metabolism-associated biological processes, including the purine ribonucleotide, monocarboxylic acid, ribonucleoside triphosphate, purine nucleoside triphosphate, and ATP metabolic processes. KEGG analysis indicated that most DLPs were also enriched in metabolism-related pathways, including glycolysis, amino acid (valine, leucine, and isoleucine) degradation, pyruvate metabolism, fatty acid degradation, and the citrate cycle. The top 20 hub proteins were screened from the PPI network based on their degree ranks. Conclusions This study revealed the role of Kla in ccRCC, which will extend our understanding of the potential molecular mechanisms underlying ccRCC formation and progression. These key Kla-modified proteins may be promising therapeutic targets for the treatment of ccRCC. However, further molecular experiments are required to validate these findings.